Effectiveness of Nanosilica on Enhancing the Mechanical and Microstructure Properties of Kenaf/Carbon Fiber-Reinforced Epoxy-Based Nanocomposites - Muruganantham Ponnusamy; L. Natrayan; S. Kaliappan; G. Velmurugan; Subash Thanappan (Adsorption Science & Technology)
With an ultrasonic frequency of 15 kHz and an 850 W power capacity, the effects of nanosilica particle inclusion on the tensile, flexural, and impact properties of woven fiber-reinforced kenaf/carbon fiber/epoxy hybrid composites were explored experimentally. The nanoparticles were dispersed uniformly in the epoxy using an ultrasonic probe. Test samples were made according to ASTM requirements for three distinct weight compositions of nanosilica particles (1, 1.5, and 2 wt%). The composites were made utilizing the compression moulding process with the following parameters: (i) weight ratio of nanosilica, (ii) length of kenaf fibers, and (iii) number of carbon fiber layers to achieve the objectives above. According to unmodified samples, with a nanosilica concentration of 1.5 wt%, tensile strength improved by 31%, flexural strength increased by 42.36%, and impact strength increased by 22.65%. It was established that the interaction of micro silica particles with epoxy and fiber, which improved interfacial tension, had a substantial impact on mechanical and water retention capabilities. The 1.5 wt% nanosilica inclusion absorbs less moisture than the 1 and 2 wt% silica composites. A scanning electron microscope was used to examine the fractured surface of the tested nanocomposites.